2009
DOI: 10.1017/s175173110800356x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the Texel muscling quantitative trait locus on carcass traits in crossbred lambs

Abstract: Texel muscling quantitative trait locus (TM-QTL) is a QTL on chromosome 18, originally identified in purebred UK Texel sheep, which was reported to increase ultrasonically measured muscle depth at the third lumbar vertebra by around 4% to 7%. The objective of the present study was to comprehensively evaluate the TM-QTL and to determine whether it could provide benefits to the UK sheep industry through increased carcass meat yield in crossbred slaughter lambs. Effects of this QTL on a range of carcass traits, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 21 publications
3
24
0
Order By: Relevance
“…The initial study by Walling et al 2004 showed an effect of +4% to +7% on ultrasound muscle depth, and in a larger population in a follow-on study Matika et al (2011) showed an effect of +8% to +17% in 6 out of 36 Texel families. This effect was confirmed in Texel sired crossbred lambs out of Mule ewes (Macfarlane et al, 2009) and also out of Welsh Mountain ewes (Masri et al, 2011). Macfarlane et al (2009) also noted that loin muscle (M. longissimus lumborum) width, area, volume and weight were also higher in lambs inheriting TM-QTL from their sire.…”
Section: Discussionmentioning
confidence: 81%
See 4 more Smart Citations
“…The initial study by Walling et al 2004 showed an effect of +4% to +7% on ultrasound muscle depth, and in a larger population in a follow-on study Matika et al (2011) showed an effect of +8% to +17% in 6 out of 36 Texel families. This effect was confirmed in Texel sired crossbred lambs out of Mule ewes (Macfarlane et al, 2009) and also out of Welsh Mountain ewes (Masri et al, 2011). Macfarlane et al (2009) also noted that loin muscle (M. longissimus lumborum) width, area, volume and weight were also higher in lambs inheriting TM-QTL from their sire.…”
Section: Discussionmentioning
confidence: 81%
“…This effect was confirmed in Texel sired crossbred lambs out of Mule ewes (Macfarlane et al, 2009) and also out of Welsh Mountain ewes (Masri et al, 2011). Macfarlane et al (2009) also noted that loin muscle (M. longissimus lumborum) width, area, volume and weight were also higher in lambs inheriting TM-QTL from their sire.…”
Section: Discussionmentioning
confidence: 81%
See 3 more Smart Citations